2008
DOI: 10.1152/ajpheart.00968.2007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of agonist-induced vasoconstriction in mouse pulmonary artery

Abstract: In recent years, transgenic mouse models have been developed to examine the underlying cellular and molecular mechanisms of lung disease and pulmonary vascular disease, such as asthma, pulmonary thromboembolic disease, and pulmonary hypertension. However, there has not been systematic characterization of the basic physiological pulmonary vascular reactivity in normal and transgenic mice. This represents an intellectual "gap", since it is important to characterize basic murine pulmonary vascular reactivity in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…Our previous histological data showed that ECs were present in the PA rings after contraction experiments (43). Perfusion of bradykinin, an endothelium-dependent vasodilator, caused a marked relaxation in mouse PA rings contracted by 40 mM K ϩ (43).…”
Section: Animals and Isolation Of Pa Rings Male 5-to 8-wk-old P75mentioning
confidence: 94%
See 2 more Smart Citations
“…Our previous histological data showed that ECs were present in the PA rings after contraction experiments (43). Perfusion of bradykinin, an endothelium-dependent vasodilator, caused a marked relaxation in mouse PA rings contracted by 40 mM K ϩ (43).…”
Section: Animals and Isolation Of Pa Rings Male 5-to 8-wk-old P75mentioning
confidence: 94%
“…Isometric tension was continuously monitored and acquired using DATAQ software (DATAQ Instruments). Resting passive tension was set at 300 mg (43), and rings were equilibrated for 1 h at resting tension and then challenged three times with 40 mM K ϩ perfusate to obtain a stable contractile response. The optimal resting (or basal) tension (300 mg) was determined by our previous study (43) showing that increasing the basal tension from 100 to 300 mg significantly augmented the 40 mM K ϩ -induced active tension in isolated mouse PA rings.…”
Section: Animals and Isolation Of Pa Rings Male 5-to 8-wk-old P75mentioning
confidence: 99%
See 1 more Smart Citation
“…Isometric tension was continuously monitored and acquired using DATAQ software (DATAQ Instruments, Akron, OH). Optimal resting tension for mouse PA and MA preparations has been previously reported to be ϳ300 mg (57,58). Unless indicated otherwise, resting tension was set at 300 mg. All the rings were equilibrated for 1 h at resting tension and then challenged three times with 40 mM K ϩ (40K) perfusate to obtain a stable contractile response (57).…”
Section: Methodsmentioning
confidence: 99%
“…Optimal resting tension for mouse PA and MA preparations has been previously reported to be ϳ300 mg (57,58). Unless indicated otherwise, resting tension was set at 300 mg. All the rings were equilibrated for 1 h at resting tension and then challenged three times with 40 mM K ϩ (40K) perfusate to obtain a stable contractile response (57). Isolated rings were superfused with modified Krebs solution (MKS; at 37°C) consisting of the following (in mM): 138 NaCl, 1.8 CaCl 2, 4.7 KCl, 1.2 MgSO 4, 1.2 NaH2PO4, 5 HEPES, and 10 glucose (pH 7.4 with NaOH).…”
Section: Methodsmentioning
confidence: 99%